História a múltiplas mãos: tempo presente, história pública e interdisciplinaridade (Tempo e Argumento, 2022)
Interview with researcher Luc Capdevila, made by Mariana Joffily and Caroline Jaques Cubas.
Keywords: interview; present time; public history; interdisciplinarity